Grocery store interventions to change food purchasing behaviours: a systematic review of randomized controlled trials - Hartmann-Boyce, J; Bianchi, F; Piernas, C; Payne-Riches, S; Frie, K; Nourse, R; Jebb, S (Oxford University Press, 2018)
Background Diet is an important determinant of health, and food purchasing is a key antecedent to consumption. Objective We set out to evaluate the effectiveness of grocery store interventions to change food purchasing, and to examine whether effectiveness varied based on intervention components, setting, or socioeconomic status (SES). Design We conducted a systematic review of randomized controlled trials (search 6/2017). Studies must have: aimed to change food purchasing; been implemented in grocery stores (real or simulated); reported purchasing; and had a minimal control or compared interventions fulfilling our criteria. Searching, screening, bias assessment and data extraction followed Cochrane methods. We grouped studies by intervention type (economic, environmental, swaps, and/or education), synthesised results narratively, and conducted an exploratory qualitative comparative analysis (QCA). Results We included 35 studies representing 89 interventions, >20,000 participants, and >800 stores. Risk of bias was mixed. Economic interventions showed the most promise, with eight of the nine studies in real stores and all six in simulated environments detecting an effect on purchasing. Swap interventions appeared promising in the two studies based in real stores. Store environment interventions showed mixed effects. Education-only interventions appeared effective in simulated environments but not in real stores. Available data suggested that effects of economic interventions did not differ by SES, whereas for other interventions impact was variable. In our QCA, economic interventions (regardless of setting) and environmental and swap interventions in real stores were associated with statistically significant changes in purchasing in the desired direction for at least one of the foods targeted by the intervention, while education-only interventions in real stores were not. Conclusions Findings suggest interventions implemented in grocery stores – particularly ones which manipulate price, suggest swaps, and perhaps manipulate item availability – have an impact on purchasing and could play a role in public health strategies to improve health.